Cement layer thickness and load-bearing capacity of tooth restored with lithium-disilicate glass ceramic and hybrid ceramic occlusal veneers - Yli-Urpo, Topias; Lassila, Lippo; Närhi, Timo; Vallittu, Pekka (Elsevier BV, 2025)
OBJECTIVES
To evaluate the influence of cement layer and veneer thickness on load-bearing capacity of tooth restored with hybrid ceramic (HC) and lithium-disilicate glass ceramic (LDGC) occlusal veneer restorations.
METHODS
Cement layer thickness was set at either 50 µm or 200 µm and tooth restored either with 0.5 mm or 1.8 mm thick HC Cerasmart270 (GC) or LDGC IPS e.max CAD (Ivoclar Vivadent) occlusal veneers. For this study, 64 extracted human molar teeth were selected and divided into 8 groups. Prepared teeth were scanned, and occlusal veneers were manufactured using CAD/CAM technology (Cerec, Dentsply-Sirona). Finished veneers were luted to preparations using self-adhesive resin cement (G-CEM ONE) according to manufacturers' instructions. Teeth were loaded quasi-statically and ultimate fracture loads were recorded. Fracture types were analyzed and classified visually. Statistical analysis was performed using two-way ANOVA.
RESULTS
With HC occlusal veneers, thickness of both veneer and cement layer had no significant influence on fracture load. The lowest mean ultimate fracture load value was found in 0.5 mm thick LDGC veneers group with 200 µm cement layer, which was significantly lower loading value compared with that of 1.8 mm thick LDGC veneers or any of HC veneers (p ≤ 0.0280). LDGC veneers with 0.5 mm thickness showed fractures within the veneer, whereas in other groups fractures of the tooth substance was also detected.
CONCLUSIONS
Within the limitations of this study, it can be concluded that thin HC occlusal veneers provided higher load-bearing capacity than LDGC counterparts of the same thickness. HC veneers were also less sensitive to the effect of cement layer thickness.